Corporate rehabilitation: informal corporate rescue mechanisms for troubled companies in the United Kingdom and Malaysia - Azmi, Ruzita; Abd Razak, Adilah (Universiti Putra Malaysia Press, 2014)
Corporate insolvency law aims to provide instruments of corporate survival or rescue. The revival of companies on the brink of economic collapse may involve rescue procedures that go beyond the normal managerial responses to corporations in distress and they may operate through both informal mechanisms and formal legal procedures. Most importantly only viable companies and businesses deserve to be rescued. There are various types of rescue actions to turnaround corporate fortunes at a time of corporate crisis. This could be in the form of a broad range of restructuring activities. This article examines the informal rescue practices and mechanisms available to troubled companies in the UK and Malaysia. Some common rescue mechanisms that are discussed include sell-offs, management buy-out (MBO), debt for equity conversion, retrenchment, redundancy as well as ‘workout’ arrangements to restructure debts owed by companies to banks or creditors.